Analisis Tingkat Kesehatan Bank Dengan Menggunakan Metode RGEC (Risk Profile, Good Corporate Governance, Earning Dan Capital) Yang Terdaftar Di BEI - Khofi Dhotur Rodiyatum Masruro; Seger Priantono; Dyah Ayu Perwitasari (JUMAD : Journal Management, Accounting, & Digital Business, 2023)
The development of a country's economy is inseparable from the condition and performance of the banking sector. Banking plays an important role in supporting the Indonesian economy because banks are one of the drivers of the country's economy and part of the financial system. In accordance with Law Number 7 of 1992 concerning banking as amended by Law Number 10 of 1998, banks are required to maintain their health. The purpose of this researcher is to analyze and summarize the soundness level of state-owned commercial banks from 2017 to 2020 based on the RGEC method, so that it can be determined which bank has the best title among several state-owned banks. The type of research used is descriptive quantitative, the variables used are Risk Profile, Good Corporate Governance, Earnings, and Capital. The data used is from 2017-2021. The results showed that NPL values ​​were categorized as unhealthy, LDR values ​​were categorized as unhealthy, GCG values ​​were categorized as very healthy, ROA values ​​were categorized as very healthy, ROE values ​​were categorized as unhealthy, NIM values ​​were categorized as very healthy, BOPO values ​​were categorized as very healthy and CAR values ​​were not categorized. Healthy.